Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
In this case, since one equation is in the form of x=, substitution would be best for this problem. Simply plug in 4y + 8 in place of x in the second equation, solve for y, then plug that value into the first equation to find x.
X=4y+8
2x-8y=-3
lets use the substitution method
2x-8y=-3
2(4y+8)-8y=-3
8y+16-8y=-3
16 is not equal to -3 so lets try elimination
x=4y+8
2x-8y=-3
xhange the 1st equation to standard for
x-4y=8
2x-8y=-3
multiply the 1st equation to remove x
2x-8y=8
2x-8y=-3
0 is not equal to 11
therefore we cannot solve using both equations so te question's answer is undefined
2x-8y=-3
lets use the substitution method
2x-8y=-3
2(4y+8)-8y=-3
8y+16-8y=-3
16 is not equal to -3 so lets try elimination
x=4y+8
2x-8y=-3
xhange the 1st equation to standard for
x-4y=8
2x-8y=-3
multiply the 1st equation to remove x
2x-8y=8
2x-8y=-3
0 is not equal to 11
therefore we cannot solve using both equations so te question's answer is undefined
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.